Moral Value of Novel “Almond” Written By Shon Won Pyung - Prima Danti Aulia; Marudut Bernadtua Simanjuntak (BADAN PENERBIT STIEPARI PRESS, 2022)
Almond is a phenomenal novel written by Sohn Won Pyung. Almond himself tells about a child who has alexthymia disorder in his brain. This novel tells the life of a person named Yoonjae who cannot feel various kinds of emotions . Almond 's novel itself does not only focus on his struggle against Alexthymia disorder but also tells the twists and turns of his life. The Almond novel is a psychological novel with the theme of mental health so that in it there are many moral messages that can be taken. Moral itself is a human behavior, where the parameters depend on the values and rules held by society in each environment. Morals are the difference between good and bad. The author will examine the novel Almond by using a qualitative approach with a descriptive method. The author uses primary and secondary data, where the primary data is taken from the analysis of reading the novel repeatedly, while the secondary data is taken through the internet. The author reads the novel Almond and then pays attention to the behavior and character of the characters, then the data is analyzed so that it can be presented in this paper.